The Impact of Attitudes on Career Adaptability: Analysis of Organizational Citizenship Behavior as an Intervening Variable - Riduwan Riduwan (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
The purpose of this study is to assess how important attitudes are in relation to the career adaptability of PT. Lima Berjaya Persada Kutorejo - Mojokerto. The respondents in this study who work at PT. Lima Berjaya Persada Kutorejo - Mojokerto, was given a total of 49 questionnaires. Saturated sampling and sampling methods used in this kind of quantitative research. As a result, 49 employees were used as research samples. The data analysis method used is descriptive statistical analysis, especially the SEM-PlS test. Software called Smart Pls 4.0 is used to help with data processing. Analysis of external models (measurement models) used to analyze data. This study uses validity and reliability tests. The following in-depth analysis of the model (structural model evaluation) includes model quality testing (fit model), the use of a bootstrapping approach to test hypotheses, and cross-validation redundancy assessment (Q2). The test results showed that: 1) attitude had a significant and positive influence on Organizational Citizenship Behavior; 2) attitudes have a considerable influence on career adaptability; and 3) organizational citizenship behavior has a great influence on career adaptability. This study provides additional information for interested parties in the world of work about the influence of attitude on career adaptability through organizational citizenship behavior (ocb) of PT. Lima Berjaya Persada Kutorejo- Mojokerto. In addition, this research is also expected to be a guideline, reference, or reference for future research, The results of this research are expected to be useful for readers and add insight about the influence of attitude on career adaptability through the organizational citizenship behavior (ocb) of PT. Lima Berjaya Persada Kutorejo – Mojokerto.